2020
DOI: 10.1016/j.chaos.2019.109471
|View full text |Cite
|
Sign up to set email alerts
|

Soliton dynamics in a fractional complex Ginzburg-Landau model

Abstract: The general objective of the work is to study dynamics of dissipative solitons in the framework of a one-dimensional complex Ginzburg-Landau equation (CGLE) of a fractional order. To estimate the shape of solitons in fractional models, we first develop the variational approximation for solitons of the fractional nonlinear Schrödinger equation (NLSE), and an analytical approximation for exponentially decaying tails of the solitons. Proceeding to numerical consideration of solitons in *Manuscript Click here to v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…( 22) is tantamount to a result recently reported for the cubic nonlinearity with α = 1 in Ref. [72]]. These results may be likened to the well-known VA prediction for the norm of the Townes' solitons in the 2D NLSE with the cubic selffocusing [97]:…”
Section: B Scaling Relations For Soliton Familiessupporting
confidence: 74%
See 1 more Smart Citation

Quadratic fractional solitons

Zeng,
Zhu,
Malomed
et al. 2021
Preprint
Self Cite
“…( 22) is tantamount to a result recently reported for the cubic nonlinearity with α = 1 in Ref. [72]]. These results may be likened to the well-known VA prediction for the norm of the Townes' solitons in the 2D NLSE with the cubic selffocusing [97]:…”
Section: B Scaling Relations For Soliton Familiessupporting
confidence: 74%
“…In the context of a different problem, it was recently demonstrated that VA can be used to look for localized solutions of the fractal NLSE [72,95]. To this end, we note that Eq.…”
Section: B Scaling Relations For Soliton Familiesmentioning
confidence: 95%

Quadratic fractional solitons

Zeng,
Zhu,
Malomed
et al. 2021
Preprint
Self Cite
“…In particular, the 1D Schrödinger equation with the cubic term subject to singular spatial modulation may emulate fractional dimension 0 < D < 1 [81]. Recent works have demonstrated that the fractional NLSE supports a variety of fractional spatial-soliton solutions [82]: "accessible solitons" [83]- [85], double-hump and fundamental solitons in PT -symmetric potentials [86,87], bulk and surface gap solitons in PT -symmetric photonic lattices [88]- [90], vortex solitons in PT -symmetric azimuthal potentials [91], 2D self-trapped modes [92], spontaneous symmetry breaking in a dual-core system [93], and dissipative solitons in the fractional complex-Ginzburg-Landau equation [94]. Further, the composition relation between nonlinear Bloch waves and gap solitons supported by lattices [95,96], solitons under the action of nonlinearity subject to spatially-periodic modulation [97], dissipative surface solitons [98], as well as discrete solitons [99], have also been addressed.…”
Section: Introductionmentioning
confidence: 96%
“…(12) can be solved directly by dint of conjugate gradient iterations [81,82], which yields symmetric, antisymmetric, and asymmetric soliton solutions. In fact, even in the case of α < 1, when solitons, supported by the self-focusing cubic nonlinearity in the free space, are unstable, because of the occurrence of the supercritical collapse [74], the trapping potential may stabilize the solitons and uphold the familiar SSB scenario, as shown in Fig. 3(a) for α = 0.8.…”
Section: B the Numerical Methodsmentioning
confidence: 99%